2017
DOI: 10.1002/nau.23376
|View full text |Cite
|
Sign up to set email alerts
|

Capsaicin‐induced rapid neutrophil leukocyte activation in the rat urinary bladder microcirculatory bed

Abstract: Aims: This study was initiated to investigate the involvement of neutrophil leukocyte activation in neurogenic inflammation, a process also involved in human urinary pathologies, elicited in the rat urinary bladder by the local administration of capsaicin, the archetypal TRPV1 agonist. The contribution of afferent nerves and sensory neuropeptides to leukocyte activation in the urinary bladder microcirculatory bed was examined. Methods: Following a 15-min topical application of capsaicin (50 μM), leukocyteendot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“… 31 However, topical capsaicin promotes the release of SP from bladder sensory nerves. 32 In addition, capsaicin stimulated the release of SP from rabbit dorsal root ganglion (DRG) cells cultured in vitro in a time-dependent manner. 33 In this study, we used capsaicin to inhibit the expression of SP and observed that capsaicin improved SCH, however, the underlying mechanism needs to be further demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“… 31 However, topical capsaicin promotes the release of SP from bladder sensory nerves. 32 In addition, capsaicin stimulated the release of SP from rabbit dorsal root ganglion (DRG) cells cultured in vitro in a time-dependent manner. 33 In this study, we used capsaicin to inhibit the expression of SP and observed that capsaicin improved SCH, however, the underlying mechanism needs to be further demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…In CD4 + T cells, TRPV1 was associated with T cell receptor (TCR) and facilitated TCR-induced Ca 2+ inflow (37), and the activity of CD4 + T cells was impaired via the inhibition of TRPV1 (38). The activation of TRPV1 was also reported to enhance leukocyte rolling and adhesion (39). These data indicated the possible pro-inflammatory properties of TRPV1 in immune cells.…”
Section: Trp Channels In Immune Cellsmentioning
confidence: 93%
“…Morphological analysis of the tissue from patients and animal models shows areas of leukocyte infiltration, edema, mast cells [25] and bladder wall glomerulations (‘pinpoint bleeding’) suggestive of fragile blood vessels (review [110]). A recent study using intravital microscopy methods imaged in vivo interactions between leukocytes and endothelial cell in the microcirculatory system following capsaicin application to the serosa surface of the bladder [111]. The experiments revealed a rapid (within 15 minutes after application) and long lasting (over 45 min) increase in the dynamic of leukocyte rolling and adhesion to endothelial cells accompanied by increased immunoreactivity for the adhesion proteins E-selectin and ICAM-1.…”
Section: Pathophysiology Animal Models and Links To Human Conditionmentioning
confidence: 99%
“…Leukocyte rolling was prevented by a CGRP receptor antagonist (CGRP8-34) but not by an NK1 receptor antagonist (RP67580), while the adhesion was prevented by blocking either CGRP or NK1 receptors. Taken together, these findings suggest that the dynamics and extent of neurogenic inflammation processes depend not only on the density of the TRPV1 positive fibers, but also on other factors such as the density of CGRP receptors and the expression of adhesion molecules in the tissue [111]…”
Section: Pathophysiology Animal Models and Links To Human Conditionmentioning
confidence: 99%